Analisis Partisipasi Masyarakat dalam Program Perhutanan Sosial (Studi Kasus di Kabupaten Sanggau Propinsi Kalimantan Barat) - Emi Roslinda; Reny Rianti; Herculana Ershinta (Faculty of Forestry Universitas Gadjah Mada, 2022)
As one of the benchmarks for the success of the Community Forestry (HKm) program, participation provided access and increased the capacity to manage state forests. HKm in Sanggau District was initiated and facilitated by various parties with intensive and sustainable empowerment activities. Therefore, this research aimed to analyze participation in managing state forests in the HKm scheme. The level was measured using the Arnstein participation concept in the planning, implementation, and evaluation stages. Data were collected through in-depth interviews, questionnaire distribution, and document reviews, and the analysis employed a qualitative descriptive approach with descriptive statistics. The participation forms included thoughts, ideas, suggestions, and energy contributions to planning, implementation, and evaluation activities. The result showed that the participation level in the research area was in the delegated power stage, through projects/activities conducted by external parties to achieve specific goals.